2000
DOI: 10.1001/archpsyc.57.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temporal Variability on P50 and the Gating Ratio in Schizophrenia

Abstract: These findings suggest that temporal variability contributes significantly to the P50 response as measured using the gating procedure. The measure of temporal variability may provide a new index of inhibitory and attentional function in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
44
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 60 publications
14
44
0
1
Order By: Relevance
“…Such increase was found in all groups of patients with epilepsy, regardless of seizure control. In agreement with the results reported here, several authors have found that the decrease in P50 suppression in patients with schizophrenia is due to a smaller amplitude of S1, although some increase in the amplitude of S2 has also been reported 11,[17][18][19][20] . One possible explanation is that there may be a direct effect on the inhibition of the response to the second stimulus in epilepsy, thus leading to greater amplitude of S2.…”
Section: Age Range and Mean Age±standard Deviation (Yearssupporting
confidence: 93%
See 1 more Smart Citation
“…Such increase was found in all groups of patients with epilepsy, regardless of seizure control. In agreement with the results reported here, several authors have found that the decrease in P50 suppression in patients with schizophrenia is due to a smaller amplitude of S1, although some increase in the amplitude of S2 has also been reported 11,[17][18][19][20] . One possible explanation is that there may be a direct effect on the inhibition of the response to the second stimulus in epilepsy, thus leading to greater amplitude of S2.…”
Section: Age Range and Mean Age±standard Deviation (Yearssupporting
confidence: 93%
“…The sensory filter depends on complex brain circuits. In schizophrenia, the decrease in the S2/S1 ratio is usually due to a decrease in S1 amplitude 11,[17][18][19][20] , whereas in other disorders, such as Machado-Joseph disease 18 and traumatic brain injury 4 , S2 amplitude is increased, which may indicate the existence of different mechanisms affecting the sensory filter.…”
mentioning
confidence: 99%
“…Our hypothesis was based on evidence implicating glutamatergic and cholinergic receptors in sensory gating (Adler et al, 1986;Luntz-Leybman et al, 1992;Miller et al, 1992a;Bickford and Wear, 1995) and on data showing that cortical and CSF KYNA levels are elevated in schizophrenia (Erhardt et al, 2001;Schwarcz et al, 2001), a disorder characterized by marked auditory gating deficits (Adler et al, 1982;Boutros et al, 1991;Jin et al, 1997;Clementz et al, 1998a, b;Patterson et al, 2000). Since KYNA penetrates the bloodbrain barrier very poorly (Fukui et al, 1991), an indirect approach was implemented, involving blockade of the PBCD-sensitive transporter alone and in conjunction with the administration of KYNA's immediate bioprecursor KYN.…”
Section: Discussionmentioning
confidence: 99%
“…Altered responsiveness to auditory stimuli has also been observed in humans. Thus, several laboratories have reported that the amplitude of the conditioning response is significantly reduced in schizophrenic patients (Jin et al, 1997;Patterson et al, 2000;Blumenfeld and Clementz, 2001). Moreover, in normal controls, the amplitude of the conditioning response is more tightly correlated with other indices of sensory gating (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation